Effect of Covi-soup on Random Blood Sugar and Blood Pressure among Patients with Type II Diabetes and Hypertension in Kenya - Sagam, Caleb Kimutai; Kivelenge, Antonette; Mutuli, Lucy; Situma, Jane (Al-Sihah: The Public Health Science Journal, 2023)
Non-communicable diseases (NCDs) are posing a serious global challenge due to the high impact on health and mortality. These diseases are becoming more prevalent in low and middle-income countries. Therefore, this study aimed to test the effect of Covi-soup on random blood sugar (RBS) and blood pressure among patients with type II diabetes mellitus and hypertension. This was a pilot study conducted in Kakamega County, Kenya. Simple systematic sampling was used in identifying respondents and allocating them to the groups. A total of 64 respondents were involved in this study, with 34 and 30 assigned to the treatment and control groups. The treatment group received Covi-soup, containing butternut squash, ginger, garlic, sunflower pepper, chia seeds, and turmeric, while the control consumed a rice soup. There was no significant difference in baseline RBS and systolic pressure levels in the treatment and control with (P =0.909) and (P =0.218), respectively. There was no positive change in RBS, but a positive change was reported in systolic and diastolic blood pressures (P ≤0.187), (P ≤0.012), and (P ≤0.001) after an intervention. Furthermore, there was a significant difference in RBS, systolic blood pressure, and diastolic blood pressure values of the treatment and non-treatment. The consumption of Covi-soup by patients with type II diabetes mellitus and hypertension for 3 months resulted in reduced blood pressure and random blood sugar levels.